2018
DOI: 10.3324/haematol.2017.184481
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective and pro-angiogenic functions of thrombomodulin are preserved in the C loop of the fifth epidermal growth factor-like domain

Abstract: We previously found that the fifth epidermal growth factor-like domain of thrombomodulin (TME5) exerts cytoprotective and pro-angiogenic functions via G-protein coupled receptor 15 (GPR15). TME5 is comprised of three S-S bonds that divide it into three loops: A (TME5A), B (TME5B), and C (TME5C). Herein we identified the minimum structure of TME5 that produces favorable effects in vascular endothelial cells (ECs). We found that TME5C, composed of 19 amino acids, but not TME5A or TME5B, stimulated the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…For example, recombinant thrombomodulin (rTM) is approved in Japan to treat disseminated intravascular coagulation (DIC) and has been shown to reduce SOS and the occurrence of thrombotic microangiopathy in HSCT patients [162,163]#. In two murine SOS models, one using monocrotaline (MCT) and the other using busulfan/cyclophosphamide conditioning followed by HSCT, rTM’s cytoprotective effect was demonstrated to depend on its fifth epidermal growth factor-like region (TME5) [164,165]#. A murine model of tacrolimus-induced vascular injury showed that the pro-angiogenic functions of TME5 depended on its binding to G protein-coupled receptor (GPR) 15 [165,166]#.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recombinant thrombomodulin (rTM) is approved in Japan to treat disseminated intravascular coagulation (DIC) and has been shown to reduce SOS and the occurrence of thrombotic microangiopathy in HSCT patients [162,163]#. In two murine SOS models, one using monocrotaline (MCT) and the other using busulfan/cyclophosphamide conditioning followed by HSCT, rTM’s cytoprotective effect was demonstrated to depend on its fifth epidermal growth factor-like region (TME5) [164,165]#. A murine model of tacrolimus-induced vascular injury showed that the pro-angiogenic functions of TME5 depended on its binding to G protein-coupled receptor (GPR) 15 [165,166]#.…”
Section: Resultsmentioning
confidence: 99%
“…In two murine SOS models, one using monocrotaline (MCT) and the other using busulfan/cyclophosphamide conditioning followed by HSCT, rTM’s cytoprotective effect was demonstrated to depend on its fifth epidermal growth factor-like region (TME5) [164,165]#. A murine model of tacrolimus-induced vascular injury showed that the pro-angiogenic functions of TME5 depended on its binding to G protein-coupled receptor (GPR) 15 [165,166]#. rTM was able to mitigate aGvHD in mice in a GPR15-dependent manner [167]#.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the recombinant thrombomodulin fragment TMD23 (with a 6-tandem EGF-like domain and O-glycosylation site-rich domain) was reported to stimulate angiogenesis (63,74). The C loop of the C-terminal sub-domain of the fifth EGF-like domain of TMD23 has pro-angiogenic and cytoprotective effects, in a G protein-coupled receptor 15-dependent manner (75). Angiogenesis was also mediated by the phosphorylation of ERK1/2, p38, protein kinase B (Akt) and Endothelial nitric oxide synthase (eNOS) (74), and by Fibroblast growth factor receptor 1-A (76).…”
Section: Thrombomodulinmentioning
confidence: 99%
“…A subsequent study revealed that this cytoprotective outcome was triggered by thrombomodulin EGF5 binding to G protein‐coupled receptor‐15 (GPR15) on endothelial cells, leading to the activation of endothelial nitric oxide synthase and extracellular signal‐regulated kinase (ERK) signalling, an effect that was abolished in GPR15‐deficient mice . Recently, the minimal fragment of thrombomodulin EGF5 necessary for binding to GPR15 and promoting proangiogenic function was identified as a 19‐amino acid peptide, that includes an intramolecular disulfide bond which adopts a loop structure similar to that observed for the prototypical EGF . This peptide exhibited proangiogenic function and extended survival in mouse models of sinusoidal obstruction syndrome, a condition that is associated with injury of liver sinusoidal endothelium .…”
Section: Thrombomodulin and Angiogenesismentioning
confidence: 99%
“…Recently, the minimal fragment of thrombomodulin EGF5 necessary for binding to GPR15 and promoting proangiogenic function was identified as a 19‐amino acid peptide, that includes an intramolecular disulfide bond which adopts a loop structure similar to that observed for the prototypical EGF . This peptide exhibited proangiogenic function and extended survival in mouse models of sinusoidal obstruction syndrome, a condition that is associated with injury of liver sinusoidal endothelium . However, whether thrombomodulin can bind to GPR15 while attached to the cell membrane, or if proteolytic processing is essential, is yet to be determined.…”
Section: Thrombomodulin and Angiogenesismentioning
confidence: 99%